MENGANALISIS PENDEKATAN SELF HEALING PADA SISTEM BERBASIS SOA DAN MICROSERVICE (PAYMENT SERVICE) - Farhan, Muhammad; Ardiansyah, Najib; Sobri, Mukhamad Asep; Alindya, Yashinta; Rismayanti, Irna; Maulana, Fandi Fajar; Asri, Jefry Sunupurwa (Innovative: Journal Of Social Science Research, 2025)
The rapid development of information technology has driven the adoption of distributed system architectures such as Service-Oriented Architecture (SOA) and Microservices, especially in the domain of digital payment services. While both approaches offer high flexibility and scalability, they also present significant challenges related to system complexity and service failure risks. This study aims to analyze the implementation of self-healing system concepts in addressing these challenges. A qualitative descriptive method is employed through literature reviews, technical documentation analysis, and industry case studies. The results reveal that implementing self-healing systems using techniques such as real-time monitoring, circuit breakers, health checks, and auto-recovery significantly enhances the reliability and availability of SOA and microservices-based payment systems. Self-healing mechanisms contribute to reducing system downtime, improving resilience, and maintaining service stability in the face of disruptions or traffic spikes.